Economic and stochastic efficiency analysis of alternative cover crop systems in Louisiana. (30th October 2020) - Wang, Hua; Adusumilli, Naveen; Gentry, Donna; Fultz, Lisa
Summary: Landowners can engage in voluntary conservation with the help of incentive programs. Recommended conservation practices are selected based on management intentions as well as the contribution of those practices to the overall net returns. However, conservation motives are heterogeneous and based on individual risk behavior. Existing cost-share programs might either under-fund or over-fund conservation, which could lead to inefficient management of natural resources. The current analysis evaluates the economic feasibility of variable cover crop strategies, multiple seeding rates, within a soybean production system in silt loam and clay soils. The study utilizes stochastic efficiency with respect to a function, referred to as SERF, for determining the preferred strategies under various risk preferences. The SERF method accounts for the heterogeneity of individual decision-making with regards to conservation adoption. Results indicate that most risk-averse farmers chose tillage radish with medium seeding rate as their preferred strategy. However, as the risk-bearing capacity of an individual increases, the current level of incentives does not motivate to implement conservation. The most preferred plan for risk-neutral farmers is the fallow system in both silt loam and clay soils. The economic and risk assessment framework can improve understanding of the temporal dynamics of different practices and inform policy on conservation structure that promotes agricultural systems that are economically, environmentally, and socially sustainable.